Assessment of Social Sustainability Of Nutmeg Based-Agroindustry Supply Chain In South Aceh Regency - Trisna, Trisna; Zakaria, Muhammad; Saptari, Mochamad Ari (International Journal of Supply Chain Management, 2020)
Currently, nutmeg supply chain actors face various problems such as many damaged plants, the price of nutmeg seeds and oil which continues to decline, the processing industry has difficulty in the procurement of raw materials, and social impacts for the local community. Observing the current nutmeg commodity conditions, it need to assessment of sustainability, especially for the social dimension as a basis for improvement. This study aimed to identify social sustainability indicators, to assessment for each social sustainability indicators, and to measure the overall social sustainability index. The identification results were 19 indicators of social sustainability consisting of 7 main indicators, namely: employment, health and safety, nuisance, local community, infrastructure and resources, partnerships with stakeholders, and macro social performance. The measurement of importance weights showed that the most influential social indicator was the improvement of community welfare, then followed by the local employment. The assessment results showed that the nutmeg oil and food and beverage agroindustries, each had very poor and bad social sustainability. That is the basis for the policymakers to improve and enhance social impacts for the communities around the nutmeg supply chain.